2017
DOI: 10.3897/neobiota.33.10471
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of selectivity in introductions of mammal species worldwide

Abstract: Humans have an extremely long history of transporting and introducing mammal species outside their native geographic ranges. The characteristics of the species introduced (taxonomy, life-history, ecology, environment) can all influence which traits are available (and selected) for establishment, and subsequent invasive spread. Understanding the non-randomness in species introductions is therefore key to understanding invasions by alien species. Here, we test for selectivity in the identities and traits of mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
(76 reference statements)
1
17
0
Order By: Relevance
“…The observation that successful invasive species are hyperproductive is consistent with the suggestion that human preferences for game species or those easy to find, transport, and breed, has strongly influenced the choice of species for introduction (Capellini et al 2015). Finally, Blackburn et al (2017) showed that introduced mammal species have much larger native geographic ranges than those of randomly selected mammals, and that they originate from significantly further north in the Northern Hemisphere and from areas with higher human population densities compared to mammal species with no recorded introductions. Hence, species with human affiliations in northern latitudes of Europe were transported to North America, Australia, New Zealand, and South Africa, and generally at temperate latitudes.…”
Section: Invasive Speciessupporting
confidence: 79%
See 2 more Smart Citations
“…The observation that successful invasive species are hyperproductive is consistent with the suggestion that human preferences for game species or those easy to find, transport, and breed, has strongly influenced the choice of species for introduction (Capellini et al 2015). Finally, Blackburn et al (2017) showed that introduced mammal species have much larger native geographic ranges than those of randomly selected mammals, and that they originate from significantly further north in the Northern Hemisphere and from areas with higher human population densities compared to mammal species with no recorded introductions. Hence, species with human affiliations in northern latitudes of Europe were transported to North America, Australia, New Zealand, and South Africa, and generally at temperate latitudes.…”
Section: Invasive Speciessupporting
confidence: 79%
“…Estimates of the number of mammalian species that have been introduced have been refined in recent years, building on Long's (2003) original compilation. Capellini et al (2015) and Blackburn et al (2017) identified 232 and 306 mammal species, respectively, as having been introduced to areas outside their native distributions (representing 2.6% and 4.7% of mammal species, respectively). Using the same data, Clout and Russell (2008) estimated that 124 mammal species had established self-sustaining wild populations in at least one location outside their natural range, thereby qualifying as successful invaders.…”
Section: Invasive Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency for introduced species to be larger-bodied than expected by chance is also found for amphibians (Tingley et al 2010) and mammals (Capellini et al 2015, Blackburn et al 2017), although we currently await analyses of spatial variation in alien body mass for these taxa. As far as we are aware, the only other study to explore Bergmann's rule in the context of alien species is by Blanchet et al (2010) for fish assemblages worldwide.…”
Section: Discussionmentioning
confidence: 86%
“…This will not just be true for birds, given that we know that introduced species are a non-random selection of other taxa as well (e.g. Tingley et al 2010;Capellini et al 2015;Allen et al 2017;Blackburn et al 2017;Pyšek et al 2017). Alien macroecology is unlikely to provide many insights into species responses to the environment without this information.…”
Section: Colonization Pressure and Alien Species Distributionsmentioning
confidence: 99%